2013
DOI: 10.1007/s00125-013-2891-3
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid impairs glucose homeostasis and inhibits insulin secretion in high-fat diet obese mice

Abstract: Aims/hypothesis Lysophosphatidic acid (LPA) is a lipid mediator produced by adipocytes that acts via specific Gprotein-coupled receptors; its synthesis is modulated in obesity. We previously reported that reducing adipocyte LPA production in high-fat diet (HFD)-fed obese mice is associated with improved glucose tolerance, suggesting a negative impact of LPA on glucose homeostasis. Here, our aim was to test this hypothesis. Methods First, glucose tolerance and plasma insulin were assessed after acute (30 min) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 33 publications
5
76
0
Order By: Relevance
“…These findings reveal that modulation of LPA 3 could be considered as a new therapeutic strategy for obesity-induced insulin resistance. Moreover, Rancoule et al have shown that treatment of high fat diet fed mice with Ki16425 increased glycogen content in hepatocytes which is also in agreement with our findings demonstrating the negative effect of LPA 3 in modulation of insulin-induced glycogen synthesis [11]. However, it should be mentioned that an opposite role of LPA on glucose mobilization has been reported in muscle and adipose tissue.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings reveal that modulation of LPA 3 could be considered as a new therapeutic strategy for obesity-induced insulin resistance. Moreover, Rancoule et al have shown that treatment of high fat diet fed mice with Ki16425 increased glycogen content in hepatocytes which is also in agreement with our findings demonstrating the negative effect of LPA 3 in modulation of insulin-induced glycogen synthesis [11]. However, it should be mentioned that an opposite role of LPA on glucose mobilization has been reported in muscle and adipose tissue.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with these findings, Rancoule et al demonstrated that exogenous injection of LPA in mice induced an acute failure in glucose tolerance. A reduced insulin secretion in response to LPA was discussed as a possible mechanism for the hyperglycemic condition after LPA supply [11]. Nevertheless, our results provide evidence that the effect of LPA on insulin signaling in hepatocytes is a considerable determinant that also contributes to an impaired glucose utilization after LPA injection.…”
Section: Discussionmentioning
confidence: 66%
“…However, modulations of a specific GPCR have limits, as diseases are commonly driven by the simultaneous involvement of multiple receptors. Our study identifies Gα13 as the signaling node that regulates metabolic adaptation to extracellular stimuli, as supported by our findings that Gα13 levels in skeletal muscle were repressed by exercise, but increased under metabolic disease conditions, and that the genetic KO facilitated the reprogramming vides metabolic benefits such as the attenuation of diet-induced obesity and atherosclerosis development in mice (51,52). Inhibitors selectively targeting Rock2 or Ser243 phosphorylation of NFATc1 can also be attractive therapeutic candidates for metabolic diseases, as has already been observed in part with a nonselective Rock inhibitor (53).…”
Section: Discussionsupporting
confidence: 77%
“…LPA has been shown to lower glucose levels in normal and type I diabetic mice, though LPA production was unaltered (276). Furthermore, administration of LPA to obese prediabetic glucoseintolerant mice inhibited insulin secretion and lowered glucose tolerance (277,278). This effect was prevented by the antagonist Ki16425.…”
Section: Obesitymentioning
confidence: 99%